A wide visible light driven complex perovskite Ba(Mg1/3Ta2/3)O3−xNy photocatalyst for water oxidation and reduction. Issue 35 (25th August 2017) - Cui, Junyan; Liu, Taifeng; Qi, Yu; Zhao, Dan; Jia, Mingjun; Liu, Gang; Zhang, Fuxiang; Li, Can
Abstract : A new nitrogen-doped metal oxide photocatalyst Ba(Mg1/3 Ta2/3 )O3− x N y (BMTON) with an absorption edge of ca. 560 nm was synthesized, showing obvious H2 or O2 -evolution half reaction activities under visible light irradiation for promising solar water splitting. Abstract : The development of potential photocatalysts that can harvest visible light and drive the two half reactions of water splitting is of vital importance in solar energy utilization. Here we report a new deep nitrogen-doped complex perovskite metal oxide Ba(Mg1/3 Ta2/3 )O3− x N y (denoted as BMTON) that shows a wide visible light response with an absorption edge of ca. 560 nm rather than a shoulder absorption. Various characterizations indicate that the greatly extended light absorption is mainly ascribed to the efficient nitrogen doping into the oxide precursor Ba(Mg1/3 Ta2/3 )O3 (denoted as BMTO) that can be simply understood as lattice Mg partly substituted BaTaO x . Meanwhile, theoretical results demonstrate that the weakened Ta–O bonds of the oxide precursor by the substitution of Mg atoms with lower electronegativity than Ta atoms are responsible for the enhanced nitrogen permeation. After loading of cocatalysts Pt or CoO x, BMTON is active for H2 and O2 evolution under visible light irradiation in the presence of CH3 OH and AgNO3, respectively. This work may open a new avenue to prepare nitrogen-doped metal oxides with wide visible light utilization for potential solar energy conversion by choosing suitable precursor oxides for nitridation.